2012
DOI: 10.5665/sleep.1642
|View full text |Cite
|
Sign up to set email alerts
|

The Consensus Sleep Diary: Standardizing Prospective Sleep Self-Monitoring

Abstract: The Consensus Sleep Diary was the result of collaborations with insomnia experts and potential users. The adoption of a standard sleep diary for insomnia will facilitate comparisons across studies and advance the field. The proposed diary is intended as a living document which still needs to be tested, refined, and validated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
960
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 1,640 publications
(1,033 citation statements)
references
References 15 publications
4
960
0
7
Order By: Relevance
“…This is a common phenomenon in research on older adults, and a recent study found that older adults, particularly if they were using benzodiazepines, showed deterioration in sleep quality over a 1-year period. 42 Improvements in patient-reported outcomes were modest, with only one PSQI component (daily disturbances) showing significantly better (lower) scores in the SIP condition at the 4-month follow-up but not at post-treatment. It is possible that, given the duration of sleep difficulties for many of these older patients, sustained improvements in sleep were needed before patients began to feel better during the daytime hours.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This is a common phenomenon in research on older adults, and a recent study found that older adults, particularly if they were using benzodiazepines, showed deterioration in sleep quality over a 1-year period. 42 Improvements in patient-reported outcomes were modest, with only one PSQI component (daily disturbances) showing significantly better (lower) scores in the SIP condition at the 4-month follow-up but not at post-treatment. It is possible that, given the duration of sleep difficulties for many of these older patients, sustained improvements in sleep were needed before patients began to feel better during the daytime hours.…”
Section: Discussionmentioning
confidence: 93%
“…We also were not able to obtain completed sleep diaries, which are typically used in studies of behavioral treatments for insomnia. We asked the first 11 enrolled participants to complete a daily sleep diary based on the American Academy of Sleep Medicine consensus sleep diary 42 during their baseline assessment, and none of the patients fully completed the diary during the 3-day baseline. As a result, we used a very simple four-item diary (bedtime, rise time, sleep quality, and daytime sleepiness), which did not allow for computation of traditional sleep diary measures such as sleep efficiency or total sleep time from daily diaries but could be used for actigraphy scoring and to establish adherence to the assigned sleep schedule in the SIP program.…”
Section: Discussionmentioning
confidence: 99%
“…Daily monitoring of sleep takes place throughout treatment using the Consensus Sleep Diary. 23 The sleep diary is used for assessing baseline sleep patterns, tracking change over time, and setting and adjusting the time spent in bed. The Insomnia Severity Index (ISI 24 ) is also part of the continued assessment.…”
Section: The Va Cbt-i Protocolmentioning
confidence: 99%
“…Sleep diaries have been recommended as a useful way of prospectively assessing treatment effects within insomnia research [35,41] and provide reliable data due to being less susceptible to memory bias than retrospective reports over a longer duration. Furthermore, it has been found recently that perceptions of sleep, measured by sleep diaries, can predict following day fatigue in CFS [9], whereas objective sleep was not a significant predictor.…”
Section: Measurement Of Sleep Outcomesmentioning
confidence: 99%